An inter-disciplinary approach to airborne electromagnetics (AEM) survey design for groundwater exploration using the Australian Geoscience Data Cube and Morphotectonics. Issue 1 (1st December 2016) - Lawrie, Ken; Brodie, Ross S.; Magee, John; Tan, Kok Piang; Halas, Larysa; Mueller, Norman; Lymburner, Leo; Christensen, Niels B.
Abstract : Over the past decade, advances in new satellite and airborne sensor technologies provide an opportunity for rapid multi-scale mapping, measurement and monitoring of the physical state of the crust, including resolution of key elements of surface and sub-surface hydrological systems. These advances have been mirrored by the development in advanced computational research infrastructure which is now giving the groundwater research community access to high-resolution (spatial and temporal) biophysical datasets (e.g. climate, ecology, geoscience and geospatial) relevant to broader hydrological systems understanding. This infrastructure facilitates integration of multiple datasets and rapid and improved signal processing, inversion, and sophisticated analysis. These datasets provide a catalyst for collaboration, with inter-disciplinary approaches enabling new discovery science in a 'big data' environment, and enabling the qualitative and quantitative analysis and modelling of landscape and hydrological system processes. In Australian landscapes, airborne electromagnetics (AEM) is widely used in near-surface (<200m) groundwater investigations due to the ability to acquire consistent, spatially coherent information of high quality using calibrated systems, in very short timeframes. This study reports on an evolving inter-disciplinary approach to AEM survey design for groundwater exploration. Recent investigations have employed time series analysis of surface water availability (using the Australian Geoscience Data Cube (AGDC)) combined with morphotectonic analysis of digital elevation datasets, tectonic analysis, and geomorphic analysis of satellite optical data, to help predict preferential recharge zones and shallow groundwater resources. This novel approach has been used successfully for groundwater exploration in the western Murray Basin and Kimberley Region of northern Australia.